Prompts for interns’ critical reflections (PIR) / Mazliyana Zainal Arifin, Nor Shidrah Mat Daud and Zamnah Husin - Zainal Arifin, Mazliyana; Mat Daud, Nor Shidrah; Husin, Zamnah (Universiti Teknologi MARA, Kedah, 2023)
In order to be relevant in the working world, employees are expected to have specific skills with one of the top three being problem solving skills. It is widely known that to acquire problem solving skills, one should have critical thinking skills. Critical thinking skills are indispensable as the world is moving towards automation which will dominate the low- and medium-skilled jobs. Only those with highskilled jobs that require them to do a lot of thinking rather than repetitive and clerical work will still be relevant. With critical thinking skills demanded by companies, the education system should move towards producing critical graduates. In order to assist students to elevate their critical thinking skills, this study aims to develop a guidance for undergraduates in writing critical reflections on their internship experiences. The development of the instrument was done through three stages which are identification, development, and validation. In the identification stage, eight prompts were created based on Paul’s Elements of Thought. These eight prompts were then compared to the Revised Bloom’s Taxonomy under Knowledge Dimension of Metacognition and later compared to the Questioning Circle to ensure that the prompts were really able to enhance critical thinking of the interns. The instrument was then sent to three carefully selected Subject Matter Experts after they have agreed to give their feedback. The feedback obtained from two phases was thoroughly examined. Necessary amendments were made based on the feedback and the final version of the instrument was prepared.